PENGARUH RASIO CAR, NPL, BOPO, LDR, EPS TERHADAP HARGA SAHAM (Students' Journal of Accounting and Banking, 2012)
The purpose of this study to determine the effect of CAR, NPL, ROA, LDR, EPS to the stock price. This research is a kind of causal research and previous studies is the replication of the study population with no companies listed in Indonesia Stock Exchange during the period 2008-2010. Selection of the samples was done by using purposive sampling and from 28 companies acquired 23 companies sampled. The data used are secondary data. The statistical method used was multiple linear regression then tested classical assumptions.The results of this study indicate that partial EPS variables significantly  influence stock prices, and partially CAR, NPL, ROA, LDR no significant effect on stock prices as well as simultaneously both variable CAR, NPL, ROA, LDR, EPS significantly influence stock prices the banking companies listed in Indonesia Stock Exchange.Keywords: CAR, NPL, ROA, LDR, EPS and Stock Price